Long-term efficacy and safety of switching from lamivudine + adefovir to tenofovir disoproxil fumarate in virologically suppressed patients. Issue 5 (May 2017) - Fasano, Massimo; Maggi, Paolo; Leone, Armando; Volpe, Anna; Fiore, Jose Ramon; Angarano, Gioacchino; Santantonio, Teresa Antonia
Abstract: Background and Aim: Tenofovir disoproxil fumarate (TDF) is recommended as first-line monotherapy for nucleos(t)ide (NA)-naïve chronic hepatitis B (CHB) patients and as a second-line rescue therapy for NA-experienced patients with a previous treatment failure. However, data regarding the efficacy of TDF monotherapy in patients with lamivudine resistance (LAM-R) successfully treated with LAM + adefovir (ADV) are limited. Herein, the efficacy and safety of switching from LAM + ADV to TDF monotherapy in clinical practice have been evaluated. Methods: Sixty LAM-R HBeAg-negative CHB patients treated with ADV add-on therapy and stable viral suppression, were switched to TDF monotherapy and prospectively evaluated for virological response, liver and renal function, and bone mineral density. Results: During a median period of 57 months of TDF monotherapy, all patients maintained a virological response, four of whom cleared HBsAg (6.6%) and discontinued treatment. Monitoring of renal function showed no case of the Fanconi syndrome, no significant alterations of median serum creatinine, eGFR and phosphate levels, although a reduction of TDF dosage was required in five patients (8.3%). Despite the stable virological suppression, five cirrhotic patients and one CHB patient developed hepatocellular carcinoma. Conclusions: Our results demonstrate the efficacy of switching to TDF monotherapy in virologically suppressed CHB patients receiving long-term LAM + ADV therapy, with a low rate of adverse events.